2017
DOI: 10.1136/bjsports-2016-096938
|View full text |Cite
|
Sign up to set email alerts
|

Do Functional Movement Screen (FMS) composite scores predict subsequent injury? A systematic review with meta-analysis

Abstract: PROSPERO registration number CRD42015025575.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(140 citation statements)
references
References 85 publications
6
128
0
6
Order By: Relevance
“…As time between baseline assessment and injury occurrence increases the likelihood of confounders explaining an increase in injury risk increases. They suggest investigators consider the use of repeat assessments to improve construct validity [37].…”
Section: Discussionmentioning
confidence: 99%
“…As time between baseline assessment and injury occurrence increases the likelihood of confounders explaining an increase in injury risk increases. They suggest investigators consider the use of repeat assessments to improve construct validity [37].…”
Section: Discussionmentioning
confidence: 99%
“…36 Table 1, most participants were enlisted men who had completed at least some college coursework. The average participant had been exposed to approximately 3 types of traumatic events, had substantial combat exposure, and registered FM and balance scores that, according to published studies, 7,8,10,12,14 were within normal ranges. Nearly 4 of 5 participants endorsed a history of physical injury affecting at least 1 area of the body (eg, trunk, lower extremity).…”
Section: Methodsmentioning
confidence: 99%
“…9 Some attention has been given to measures of fundamental movement patterns and dynamic balance as univariate predictors of injury in sport participants and tactical athletes with varied results. 10 In a multivariate paradigm, however, Lehr et al 11 reported that FM characteristics combined algorithmically with injury history and bodily pain to predict injury occurrence in collegiate athletes. Bodden et al 7 showed that fundamental movements improved as a result of an 8-week ''corrective exercise program'' in mixed martial arts athletes, whereas Stanek et al 8 achieved similar results with male firefighters.…”
mentioning
confidence: 99%
“…Although the sports medicine model of injury prevention and treatment emerged to meet the special needs of competitive athletes, its applicability to problems encountered in the occupational setting has been recognized (Bigos & Davis, ; Lively, ; Larson et al., ). Because traditional methods for management of musculoskeletal injuries do not typically restore neuromuscular control to a level that minimizes risk for re‐injury and progressive dysfunction (Mottram & Comerford, ; Maffulli, Longo, Gougoulias, Loppini, & Denaro, ; Pietrosimone, McLeod, & Lepley, ; Ward et al., ), a variety of “movement efficiency” screening procedures, similar to the ones demonstrated in this study, are increasingly being used to assign scores that are widely believed to relate to both sport and occupational injury risk (Moran, Schneiders, Mason, & Sullivan, ).…”
Section: Developing Injury Risk Models For Occupational Settingsmentioning
confidence: 99%